Environmental-Friendly Fluorine Mixture for CVD Cleaning Processes to Replace C2F6, CF4 and NF3. (28th July 2016) - Wieland, Robert; Pittroff, Michael; Boudaden, Jamila; Altmannshofer, Stephan; Kutter, Christoph
Abstract : The target of this work was to find viable alternative CVD-cleaning gas mixtures for the semiconductor industry, which are environmental-friendly and in addition can be used as a "drop in" to avoid high investment costs from equipment modification. Our study has demonstrated that this can be achieved with F2 -based gas mixtures, which also provide a more efficient and faster cleaning behavior for most applications. A cleaning efficiency gain of a factor 1.3 up to 17 can be expected, relative to the F2 -amount required for cleaning. This gain in efficiency depends on the cleaning gas to be replaced and on the reactor type. A shorter cleaning time can lead into a higher equipment throughput and more cost effective usage of thin film tools. To generate data on particle and tool attrition, a first "mini marathon" test run has been performed. The test reactor, a 200mm wafer size CVD tool, was equipped with a mass spectrometer to monitor the end point of the chamber cleaning and to gain an overview of the waste gases going into the abatement system